Nälkä ja vilu (Finnish Literature Society / SKS, 2024)
This book examines a range of Arctic histories as narrative forms of telling and retelling. Most of the material – texts, images and a film – builds on the Romantic concept of the Arctic sublime. The methodological framework is that of artistic research. The concept of polarlore and themes such as a failed journey and bad food are explored from Fridtjof Nansen’s works from the 1890s and Vilhjalmur Stefansson’s books and statements from the 1920s. These are read in parallel with texts such as the travelogue of the Sami expedition member Samuel Balto and the diary of the Inuit seamstress Ada Blackjack, an original counterpoint to the male narratives of the North. Other topics include the new Arctic sublime of the 1930s as depicted in the film S.O.S. Eisberg by Arnold Fanck and in contemporary Soviet narratives of the rescue of the comrades from the sunken steamship Chelyuskin. Hunger and Cold juxtaposes new findings with critical discourses of arcticality and arcticism.